Status of Fisheries Resources and Water Quality of Tanguar Haor (Journal of Environmental Science and Natural Resources, 2015)
The study was conducted to observe the status of fisheries resource of Tanguar haor, one of the large wetland in the north eastern part of Bangladesh. For this purpose the whole study was completed in two parts: interviewing with local people and analyzing the water quality. Indiscriminate harvesting of mother fishes, use of agrochemicals, sedimentation on haor basin and habitat destruction were found as major causes of fisheries resources degradation in the study area. Most of the water quality parameters were found good which were within the standard level set by Government of Bangladesh for fisheries. However, EC and TDS were found higher than the recommended level for fish production.DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22048 J. Environ. Sci. & Natural Resources, 6(1): 103-106 2013